Peningkatan Keterampilan Menulis Teks Narasi Peserta Didik Menggunakan Model Think Talk Write Berbantuan Media Canva di Kelas IV SD Negeri 36 Cengkeh Kota Padang - Oktovia, Vivi; Desyandri, Desyandri; Suriani, Ari; Chandra, Chandra (Lembaga Intelektual Muda Maluku, 2025)
This study was motivated by the low narrative writing skills of fourth-grade students at SD Negeri 36 Cengkeh, Padang. The purpose of this research was to describe the planning, implementation, and improvement of narrative text writing skills through the Think Talk Write (TTW) model assisted by Canva media. This research employed a Classroom Action Research (CAR) design with a qualitative and quantitative approach, conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The subjects were the classroom teacher as an observer, the researcher as a practitioner, and 30 fourth-grade students. Data were collected through observation, tests, and non-test techniques, using observation sheets and test items as instruments, and were analyzed descriptively both quantitatively and qualitatively. The findings revealed improvements in all aspects: lesson planning increased from 85.4% to 95.83%; teacher performance from 82.5% to 95%; student performance from 82.5% to 95%; writing skills from 77.07 to 86.52; and knowledge scores from 62.66% to 84%. It can be concluded that the TTW model assisted by Canva effectively improves students’ writing skills. It is recommended that teachers use this model as an alternative learning strategy for teaching Indonesian language in elementary schools.